2021
DOI: 10.1109/access.2021.3103268
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Machine-Learning Algorithms Used in Wearable-Based eHealth Data Analysis

Abstract: In this digitized world, data has become an integral part in any domain, including healthcare. The healthcare industry produces a huge amount of digital data, by utilizing information from all sources of healthcare, including the patients' demographics, medications, vital signs, physician's observations, laboratory data, billing data, data from various wearable sensors, etc. With the rapid growth of the wireless technology applications, there has also been a significant increase in the digital health data. New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…In terms of what kind of ML algorithms are best suitable to work with such data, a systematic literature study conducted in [ 140 ] for ML algorithms used for eHealth applications showed the results depicted in the pie chart in Figure 6 . These results from Figure 6 are based on a systematic review of 67 scientific articles.…”
Section: Proposed Wearable-based Monitoring and Management Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of what kind of ML algorithms are best suitable to work with such data, a systematic literature study conducted in [ 140 ] for ML algorithms used for eHealth applications showed the results depicted in the pie chart in Figure 6 . These results from Figure 6 are based on a systematic review of 67 scientific articles.…”
Section: Proposed Wearable-based Monitoring and Management Solutionsmentioning
confidence: 99%
“…Other NN-based algorithms, such as Convolutional Neural Network (CNN) or Recurrent Neural Network (RNN), were mainly used for image classification but not widely encountered in the context of eHealth data. DNN and multilayer perceptron showed better performance for classification tasks for time domain and frequency domain values than other studied algorithms in [ 140 ] and references therein. Ensemble learning techniques have also been used in of studies.…”
Section: Proposed Wearable-based Monitoring and Management Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition and considering the demography of the participants in our study (i.e., the elderly), it was necessary to select the two sensors as they offered the most convenient means for the elderly to report the current state of their mood at every point in time through the use of the push buttons. In order to analyze the data from these sensors, various machine-learning algorithms were also identified in our previous study [5]. The most used machine-learning algorithms in the literature for such studies are: the gradient boosting algorithms and the XGBoost which were used, for example, in the English Longitudinal Study of Ageing (ELSA) dataset to predict the loneliness [1].…”
Section: Introductionmentioning
confidence: 99%